Peranan Kepemimpinan Kepala Desa Untuk Meningkatkan Partisipasi Masyarakat Dalam Pembangunan Desa Kadujangkung Kecamatan Mekarjaya - Nurhayati Nurhayati; M.Husein Wijaya; Jeni Minan (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research aims to determine the leadership role of the Village Head in increasing community participation in implementing development in Kadujangkung Village, Mekarjaya District, Pandeglang Regency. Data collection was carried out through observation data, interviews, and field studies, documentation, recordings. , Mekarjaya District, Pandeglang Regency, leadership is really needed to increase community participation so that local communities contribute more to development. There are still local village communities who do not have a sense of responsibility to work together to advance the village where a village will be able to progress if there is participation from own society.In realizing the vision and mission led by the village head, it takes the form of realizing Kadujangkung Village as an independent village to achieve a healthy, intelligent and more prosperous society based on faith and piety. For this reason, it is necessary to create a village government apparatus that is honest, clean, transparent and authoritative. Apart from that, improving the community's economy by empowering the community by empowering the role of BUMDES, improving community health, increasing infrastructure development, especially village road access in a sustainable manner, so that it will facilitate transportation to support the community's economy.